Population Monitoring of Diamondback Moth (Plutella Xylostella) and Evaluating Its Attacking Impact on Growth & Yield of Cauliflower at District Tando Allahyar - Memon, Hallar Arif; Nizamani, Imtiaz Ahmed; Mureed, Paras; Gul, Nasreen; Dahri, Zamin Hussain; Dahri, Shahzad Hussain (International Journal of Scientific Research in Biological Sciences, 2019)
This study was intended to evaluate the population monitoring of diamondback moth and its attacking impact on growth and yield of cauliflower, at District Tando Allahyar. The experimental site is located at 25.27570 N and 68.421500 E. Two local varieties (sathri and nawri) of cauliflower were cultivated. The population of DBM was monitored for the entire crop period using direct count and light trap methods. Twenty five plants were randomly selected for direct count observations and a light trap was installed at the field. The impact of DBM attack on growth, leaf quality and yield of cauliflower was analyzed by selecting and labelling 25 plants at the time of sowing. The results indicate that, the mean values of DBM population under direct count method was ranging from 0.24 to 2.15. The maximum (2.15) and minimum (0.24) mean values were observed on 4th and 12th (last) week, respectively. Under light trap method, the maximum and minimum DBM population was observed on the 6th and 12th week, respectively. The population trend indicates a rapid increase to gradually decrease in the number of moths. Statistically, a significant difference was observed in DBM population throughout the observations. With regard to the growth and yield of cauliflower, the results indicate that, the height of leaf was reduced by 12.38, 23.19, 35.69, 41.45 and 45.72 %, weight of leaf was reduced by 12.55, 21.24, 28.98, 40.33 and 48.93 % and the average yield of flower was reduced by 9.26 %, 17.78 %, 27.41 %, 36.11 % and 46.48 %, under the DBM attack of 2, 4, 6, 8, and 10 moths, respectively. Under leaf quality assessment, the leaf was observed with one or several colors from light green, pale, light yellow, dark yellow, brown and red. From the outcomes of this study, it is recommended that, the DBM at larvae stage highly damaged the cauliflower growth rate and reduces the crop yield. Therefore, the regular scouting of pest should be carried out and the recommended application rate of pesticides should be applied for effective management of diamondback moth particularly in cauliflower.